Great day every day : navigating life's challenges with promise and purpose - Lucado, Max; Lucado, Max. (Nashville, Tennessee : Thomas Nelson, 2012)
Describes how to make every day an extraordinary day by saturating oneself in Jesus's grace, allowing the day to be filled with God-given purpose regardless of the minor setbacks everyday life holds.
Every day deserves a chance -- Mercy for shame-filled days -- Gratitude for ungrateful days -- Forgiveness for bitter days -- Peace for anxious days -- Hope for catastrophic days -- Fuel for depleted days -- Faith for fear-filled days -- Calling for purposeless days -- Service for fork-in-the-road days -- Conclusion : the blade of uncommon color.
"Previously published as Every day deserves a chance"--Title page verso.
Includes bibliographical references.
Keywords: Christian life